FENOMENA DIFUSI LEKSIKAL UNSUR BAHASA - Wahya Wahya (Jurnal Sosioteknologi, 2011)
Linguistics lexical diffusion is a phenomenon that can occur in any language. Lexical diffusion of innovation is an element of language that spreads from the lexical to a lexical one another. Observation of lexical diffusion must begin with the observation of language lexical innovation. By observing the lexical diffusion, we can observe how the gradualism changes language elements. This shows that language change does not occur sporadically, but it was systematic. Keywords: lexical diffusion, innovation, gradualism